Analysis of Academic Supervision of School Principals in Improving the Pedagogic Competence of Teachers of Indonesian Language Classes At UPT SD Negeri 12 Arungkeke Jeneponto Regency: - - Syamsiah Syamsiah; Munirah Munirah; Ratnawati Ratnawati (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the implementation of academic supervision of school principals in improving the pedagogic competence of teachers in Indonesian subject classes at UPT SD Negeri 12 Arungkekeke, Jeneponto Regency. This study uses a qualitative approach with a descriptive type, involving the principal, three classroom teachers, and one supervisor as key informants. Data was collected through observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman's analysis model, namely data reduction, data presentation, and conclusion drawn. The results of the study show that academic supervision is carried out through three main stages, namely planning, implementation, and follow-up. The principal has prepared observation instruments, supervision schedules, and mapping teacher needs. In the implementation stage, the principal carries out classroom observations, provides constructive feedback, and guides teachers in designing teaching tools. At the follow-up stage, the principal provides further guidance through discussion, mentoring, and monitoring. Academic supervision has been proven to contribute positively to improving teachers' pedagogic competence, especially in learning planning, classroom management, and the application of methods that suit the characteristics of students. Thus, the academic supervision of school principals plays an important role in encouraging the improvement of the quality of Indonesian learning in elementary schools